Analysis Of Waste Generation Rates In Watu-Watu Village, West Kendari District, Kendari City - Finarti Finarti; La Baco Sudia; Surya Cipta Ramadhan Kete; Muhammad Saleh Qadri (International Journal of Technology and Education Research, 2026)
The objective of this study is to analyze and project waste generation in Watu-Watu Village. The research was conducted from April to July 2025. The data collection method used in this study was quantitative data. The data collection techniques employed in this study included weighing waste from 44 households, interviews with residents, observation, documentation, and a literature review. The data sources for this study were secondary data. The results of the study indicate that Watu-Watu Village consists of 1,257 households with a total population of 3,596. There are 44 households comprising 223 residents. The weight of waste generated by these 44 households is 45 kg, providing an indication of the waste weight per small household group. The weight of organic waste is 0.037 kg and inorganic waste is 0.16 kg, which are key indicators for determining the weight of organic and inorganic waste per day, month, or year. Overall, the daily waste weight per person is 0.19 kg, which is a crucial indicator for calculating waste projections per person per day. Total annual waste generation reaches 16,034,851 tons, which is an annual projection based on daily data. The conclusion of this study is that the analysis of waste generation in Watu-Watu Village shows an average household waste generation of 0.19 kg per person per day. The waste composition is dominated by inorganic waste (0.16 kg/day), which is higher than organic waste (0.037 kg/day). The total combined generation of organic and inorganic waste reaches 45 kg. The projected waste generation in Watu-Watu Village for the year 2030 is 415.53 tons/day and151,668.45 tons/year. This projection is based on population projections indicating a decrease per year from 2025 to 2030, with a population of 2,187 people in 2030.